Informal Street Food Trade: A Source of Income Generation in Urban Nepal - Adhikari, Dipak Bahadur (Economic Journal of Development Issues, 2018)
Street food trade is a growing sector in many developing countries, Nepal among them. As a means to provide low-cost food to a growing urban population of poor, unemployed people and low-wageworkers, street food trade –a predominantly self and family-based activity – has become an opportunity to generate income for many among those same urban poor living in Kathmandu Metropolitan City. On the basis of cross-sectional data collected from a sample of 50 street food vendors in two main areas of the city – namely New Bus Park and Ratna Park – this chapter analyzes the determinants affecting street food vendors’ income: whether it is correlated to vendors’ investment rates, education level, and labor supply, thus attempting to find employment and income patterns. Data are analyzed using OLS regression, and STATA- 12 statistical software. Economic Journal of Development Issues Vol. 23 & 24 No. 1-2 (2017) Combined Issue, Page : 1-17